Carotid stenting versus carotid endarterectomy: evidence basis and cost implications. - Janssen, M; de Borst, G; Mali, W; Kappelle, L; Moll, F; Ackerstaff, R; Rothwell, P; Brown, M; van Sambeek, MR; Buskens, E (2008)
OBJECTIVE: Carotid Angioplasty combined with Stenting (CAS) is increasingly performed because of its presumed benefits. A study was performed to identify key factors that determine the cost-effectiveness as compared to conventional carotid endarterectomy (CEA). METHODS: The incremental cost-effectiveness of CAS over CEA for different scenarios was estimated using a modeling approach. Treatment costs were based on actual costs of successful procedures whereas costs of complications were taken from the literature. Patient survival was modeled using the endarterectomy patients from the ECST trial. RESULTS: Procedural costs of CAS are higher than those of CEA, mainly as a result of the high material costs. Cost-effectiveness of CAS primarily depends on major stroke rates. One percent increase in the peri-operative major stroke rate causes a cost increase of 1051 euros and a loss of 0.06 quality adjusted life years. CONCLUSIONS: At present CAS is at best non-inferior to CEA in terms of clinical outcome. Cost savings due to shorter admission are offset by the high costs associated with catheter-based interventions. At present CAS should be restricted to controlled settings until clinical trials have shown a substantial clinical benefit.